Auditory decision-making deficits after permanent noise-induced hearing loss - Madeline P. Berns; Genesis M. Nunez; Xingeng Zhang; Anindita Chavan; Klavdia Zemlianova; Todd M. Mowery; Justin D. Yao (Scientific Reports)
Abstract Loud noise exposure is one of the leading causes of permanent hearing loss. Individuals with noise-induced hearing loss (NIHL) suffer from speech comprehension deficits and experience impairments to cognitive functions such as attention and decision-making. Here, we investigate the specific underlying cognitive processes during auditory perceptual decision-making that are impacted by NIHL. Gerbils were trained to perform an auditory decision-making task that involves discriminating between slow and fast presentation rates of amplitude-modulated (AM) noise. Decision-making task performance was assessed across pre- versus post-NIHL sessions within the same gerbils. A single exposure session (2 h) to loud broadband noise (120 dB SPL) produced permanent NIHL with elevated threshold shifts in auditory brainstem responses (ABRs). Following NIHL, decision-making task performance was tested at sensation levels comparable to those prior to noise exposure in all animals. Our findings demonstrate NIHL diminished perceptual acuity, reduced attentional focus, altered choice bias, and slowed down evidence accumulation speed. Finally, video-tracking analysis of motor behavior during task performance demonstrates that NIHL can impact sensory-guided decision-based motor execution. Together, these results suggest that NIHL impairs the sensory, cognitive, and motor factors that support auditory decision-making.